1997
DOI: 10.2165/00003495-199753040-00003
|View full text |Cite
|
Sign up to set email alerts
|

Cyclo-Oxygenase Isoenzymes

Abstract: The discovery of at least 2 cyclo-oxygenase (COX) isoenzymes, referred to as COX-1 and COX-2, has updated our knowledge of nonsteroidal anti-inflammatory drugs (NSAIDs). This has lead investigators to reconsider what can be awaited from this class of drugs. The 2 COX isoenzymes share structural and enzymatic similarities, but are specifically regulated at the molecular level and may be distinguished apart in their functions, although some physiological overlap between them does occur. The major goal in develop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
34
0
1

Year Published

1998
1998
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 164 publications
(35 citation statements)
references
References 189 publications
0
34
0
1
Order By: Relevance
“…Initial studies reported on the renal sparing effects of predominantly selective COX-2 inhibitors [21, 22, 23, 24, 25, 26, 27, 28, 29, 30, 31, 32]. The renal function was preserved in healthy volunteers and in patients with renal insufficiency during treatment with oxicam derivatives [26, 27, 28, 29].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Initial studies reported on the renal sparing effects of predominantly selective COX-2 inhibitors [21, 22, 23, 24, 25, 26, 27, 28, 29, 30, 31, 32]. The renal function was preserved in healthy volunteers and in patients with renal insufficiency during treatment with oxicam derivatives [26, 27, 28, 29].…”
Section: Discussionmentioning
confidence: 99%
“…Nabumetone has about 50 times selectivity for COX-2 inhibition in vitro [21], but its true COX-1 inhibitory potential in our settings has not been tested. Moreover, a rather significant role for the COX-2 isoenzyme itself in renal development and physiology has been recently identified [1].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[5][6][7]36 However, when a va- riety of cells such as macrophages and endothelial cells were challenged with various inflammatory mediators, COX-2 expression was rapidly induced. Moreover, at sites of inflammation such as the rheumatoid synovium, COX-2 was dramatically up-regulated.…”
Section: The Homeostatic Vs Proinflammatory Theory Of Cox Actionsmentioning
confidence: 99%
“…Now, it is well known that the therapeutic utility of nonselective COX inhibitors is due to inhibition of COX-2, while their side effect profile (i.e., gastrointestinal irritation and bleeding) results from inhibition of COX-1. Clearly, the development of selective inhibitors of COX-2 is an attractive target, because such agents retain the anti-inflammatory, analgesic, and antipyretic properties of nonselective COX inhibitors, while reducing the risk of gastrointestinal side effects [7][8][9]. Until recently, much attention has been focused on the design of potent and selective COX-2 inhibitors, such as celecoxib, etoricoxib and valdecoxib.…”
Section: Introductionmentioning
confidence: 99%